2006
DOI: 10.1080/00140130500321845
|View full text |Cite
|
Sign up to set email alerts
|

Different computer tasks affect the exposure of the upper extremity to biomechanical risk factors

Abstract: In order to determine differences in biomechanical risk factors across computer tasks, a repeated measures laboratory experiment was completed with 30 touch-typing adults (15 females and 15 males). The participants completed five different computer tasks: typing text, completing an html-based form with text fields, editing text within a document, sorting and resizing objects in a graphics task and browsing and navigating a series of intranet web pages. Electrogoniometers and inclinometers measured wrist and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 34 publications
4
80
1
1
Order By: Relevance
“…Mouse use is a complex motor task that requires a variety of skills (19) such as high precision (pointing), rapid movements (double clicking), coordinated hand/arm movements (dragging), and superior hand/eye coordination (pointing, dragging) (20). Studies have found that elderly mouse users tend to make more errors during mouse use than younger ones (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse use is a complex motor task that requires a variety of skills (19) such as high precision (pointing), rapid movements (double clicking), coordinated hand/arm movements (dragging), and superior hand/eye coordination (pointing, dragging) (20). Studies have found that elderly mouse users tend to make more errors during mouse use than younger ones (20).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that different mouse use tasks require different capacities (19), and therefore, mouse use training should consist of training in several skills, including accurate pointing and the ability to drag objects on a screen. Unlike keyboard use, all mouse use requires people to look at the screen while using the mouse, which may be problematic for individuals with sensory problems.…”
mentioning
confidence: 99%
“…Several studies of computer users have indicated that high intensity mouse use is associated with hand/wrist and shoulder symptoms [40][41][42] . Mouse use has been found to lead to more constrained and non-neutral postures of the wrist and shoulder compared to keyboard use 43) . Thus, a plausible explanation for the association between the high percentage of mouse use and thoracic spine pain relates to less variation in working posture during mouse use, which would potentially lead to static loading of back muscles 44) .…”
Section: Discussionmentioning
confidence: 99%
“…Although a combination of these task types is required for most desktop computer use, they require different postures and physical demands. Sustained mouse use has been linked to greater wrist extension, less postural variability, and longer duration of finger force production when compared to keyboardintensive tasks (Dennerlein & Johnson, 2006b). As a result, workers who use a mouse more than 20 hr per week have a higher prevalence of carpal tunnel syndrome (Andersen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%